Kesalahan Siswa Dalam Memecahkan Masalah Perkalian dan Pembagian Bilangan Cacah Pada Kelas III Sekolah Dasar - Setiari, Febrihana Putri; Sary, Ryky Mandar; Listyarini, Ikha (CENDEKIAWAN, 2024)
The research context that prompted this research was the low scores obtained by students on multiplication and division of whole numbers. This research aims to analyze the types of errors and factors that cause students' errors in solving multiplication and division of whole numbers based on Polya theory in class III. The data sources are class III students for the 2023/2024 academic year and class III teachers. The data in this research was obtained from test results, interviews, observation and documentation. The results of the analysis show that students experienced errors on each question with various types of errors, namely errors in understanding the problem, errors in making plans, errors in implementing plans and errors in rewriting answers. There are several causes of errors, namely students' lack of accuracy in working on the questions and students' lack of understanding the concept of the questions. Based on the research results, it can be concluded that there were four students' mistakes in solving multiplication and division of whole numbers.